توجيه متشابه بعض ألفاظ القرآن الكريم: Elucidating Select Lexically Similar Terms in the Holy Qurʾān - Abdoul Karim Toure; Mesbahul Hoque (Maʿālim al-Qurʾān wa al-Sunnah, 2024)
This study engages with a crucial aspect of Quranic exegesis that has drawn scholarly attention since the earliest periods of codification through to the contemporary era. Although much debate has revolved around whether certain Quranic terms are genuinely synonymous or simply repetitive, no definitive consensus has emerged. Rather than revisiting the well-trodden argument over the existence or non-existence of synonymy in the Qurʾān, this research focuses on selected words commonly presumed to be synonyms. By closely examining their usage and context, the study demonstrates that these terms do not share identical meanings. Instead, their semantics shift according to their placement within each verse, thereby challenging long-held assumptions and offering fresh insights into the Qur’anic text.